Modeling infrastructure interdependencies by integrating network and fuzzy set theory - Lam, C. Y. (2020)
Infrastructure interdependency refers to the bidirectional relationship between entities, and means that the state of one entity is influenced by or correlated to the state of the other. Although some interdependencies in infrastructure networks can be modeled deterministically, often the required data are incomplete or there is an element of randomness in the relationships, necessitating the use of stochastic models. In this paper, the concepts and techniques of network and fuzzy set theory are integrated, and a fuzzy modeling approach is proposed to better identify and understand interdependencies and the relationships and connections between entities in infrastructure networks. This approach will allow the topological structures and characteristics of the network to be better understood for further evaluation and analysis.